Low genetic diversity of vector-borne haemoparasites in dogs and their ticks revealed local and long-range transmission in Peninsular Malaysia - Sipin, Quincie; Mustaffa-Kamal, Farina; Watanabe, Malaika; Megat Abdul Rani, Puteri Azaziah; Abdul Aziz, Nor Azlina (Universiti Putra Malaysia, 2023)
Molecular methods coupled with phylogenetic analysis are sensitive tools for detecting and classifying parasites. This study used nuclear and mitochondrial gene markers to investigate the host-vector interaction of the vector-borne haemoparasites. The population genetic structures of important vector-borne haemoparasites in dogs, namely, Anaplasma platys, Ehrlichia canis, Babesia vogeli, and Babesia gibsoni, were determined from the nuclear gene of 16S or 18S rRNA gene, gltA and groESL and mitochondrial gene of COX1 across dogs and vector ticks. A total of 220 blood samples and 140 ticks were collected from shelter dogs in Peninsular Malaysia. Out of the positive samples for the vector-borne haemoparasites, 28 positive blood isolates and six tick isolates were selected and characterised. There was a low diversity in tick sequences, while varying degree of variability was observed in dogs’ sequences. Overlapped haplotypes were observed in sequences of dogs and ticks, revealing the possibility of the same infection origin. No regional separation was detected, but similar haplotypes from different regions were observed. These findings contribute to the epidemiology of vector-borne haemoparasites in dogs in Malaysia.